IMPROVING SCAT SINGING SKILLS DURING VOCAL JAZZ STUDIES - Inga BÄ“rziÅ†a (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
During the evolution of jazz music, vocalists in increasing frequency were trying to imitate instrumental playing in their improvisations that demonstrably was reflected in specific syllable combinations in a vocal improvisation manner of scat singing. This kind of singing allows singers to explore a much broader range of dynamic variation than had previously been possible. Such singing in jazz music allows one to express their personality in a spontaneous and ingenious way, but it must be based on a solid theoretical foundation and ask for a sistematic practical work. Aim of the Study - to analyze the process of jazz education at the university level and to propose suggestions for the acquirement of scat singing during vocal jazz studies. In order to analyze student activities, it was necessary to analyze pedagogical and psychological literature, as well as to make pedagogical observations and surveys. In performing pedagogical observations and surveys, it can be concluded that: To be a good scat singer, along with vocal technique, it is extremely important to develop precise intonation, harmonic ear, rhythm sense, improvisation skills in different jazz musical styles. Specific syllable combinations in vocal improvisation of traditional singing skills should be developed every bit as a foreign language. All these techniques should be perfected so much that a jazz vocalist could implement his thoughts and ideas straight away in a technically and artistically valuable music. Scat improvisation is a kind of art which requires musical and psychological education. Every young musician needs to know how many things are included in that process. There is a lot of knowledge that needs to be known.